The risk of foreign currency contingent claims at US commercial banks - Chaudhry, Mukesh K.; Christie-David, Rohan; Koch, Timothy W.; Reichert, Alan K. (Journal of Banking & Finance, 2000)
This study investigates the relationship between market-based measures of risk and foreign currency contingent claims activity at US commercial banks. Specifically, four types of foreign currency contingent claims are examined: purchased foreign currency option contracts, foreign-exchange swaps, commitments to purchase foreign currency and forward contracts. Within the context of the Comptroller of the Currency's (OCC’s) Banking Circular 277, we differentiate between the risk exposure of dealer banks and non-dealer banks. Empirical results suggest that (i) the use of options tends to increase all market-based measures of bank risk, (ii) swaps are used primarily for risk-control purposes and (iii) the use of forward contracts and currency commitments contributes mildly, if at all, to any type of risk. There is some evidence that swaps activity at dealer banks increases unsystematic risk. Otherwise, dealer and non-dealer banks appear to similarly manage foreign currency risk.